An educational method for evaluating the resistance to the treatment in the diagnosis of dyscalculia - Giampaolo Chiappini; Giacomo Cozzani; Shaula Verna; Cristina Potente; Fabrizio De Carli (Formare, 2016)
In this paper a didactical method that has been proven effective for evaluating the “resistance to the treatment” of the student is presented. This parameter is essential for distinguishing the learning difficulties in mathematics from the learning disorder of dyscalculia. The method is based on GimmeFive, an application that has been designed to develop skills in mental calculation of multi-digit additions and subtractions. In this paper we present the results of two experiments conducted with groups of students respectively with learning difficulties in mathematics and dyscalculia. These experiments allowed to show the effectiveness of the didactical method in the evaluation of the resistance to the treatment and to discuss the features that make it adequate for the evaluation of the learning disorder.